Spatial and temporal variation of soft-bottom peracarid (Crustacea: Peracarida) infauna in the Canakkale Strait (Turkey) - ASLAN-CIHANGIR, H.; PANCUCCI-PAPADOPOULOU, M.A. (Mediterranean Marine Science, 2011)
The biodiversity and distribution of soft-bottom peracarid crustaceans were analyzed in the south part of Canakkale Strait, a very important biological corridor between the Mediterranean and the Black Sea. Samples were collected seasonally from 11 coastal stations at depths ranging from 10 to 22 m. Moreover, qualitative samples were collected in summer from 7 stations (40 - 83 m depth) located in the middle part of the Strait. A total of 110 species were identified. Amphipods were the dominant group both in terms of species richness and abundance. Apocorophium acutum, Phtisica marina and Microdeutopus versiculatus were the most abundant species. A large number of rare species was recorded, leading to very low similarity values among stations. Six different feeding types were detected, with surface deposit feeders being the dominant one in the area. Significant differences in abundances and assemblage structure were detected along the eastern and western coasts of the Strait that could be attributed to food supply and sediment composition, depending on bottom current velocities. Possible relations of peracarids with the hydrological regime of the area are also discussed.